Introduce fair competition mechanism in China healthcare system - Wáng, Yì-Xiáng J. (Quantitative Imaging in Medicine and Surgery, 2014)
Following the economic progress, China is currently performing very well in many areas, particularly in industrial manufacturing. The number of international scientific publications has also soared. Healthcare or medical treatment is probably one of the areas where China is underperforming. Currently both patients and doctors are complaining of the healthcare system.